The existence of ϒ-fixed point for the multidimensional nonlinear mappings satisfying (ψ, θ, ϕ)-weak contractive conditions - Akhadkulov, Habibulla; Rahma Zuhra,; Azizan Saaban,; Shaddad, Fawzia; Akhatkulov, Sokhobiddin (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this paper we prove the existence of ϒ-fixed point for a multidimensional nonlinear mappings F : Xk → X defined on the partially ordered metric spaces and satisfying (ψ, θ, ϕ)-weak contractive conditions. Moreover, we prove the uniqueness of that fixed point under extra conditions to (ψ, θ, ϕ)-weak contractive conditions.